Pflege-Report 2019 2019
DOI: 10.1007/978-3-662-58935-9_13
|View full text |Cite
|
Sign up to set email alerts
|

Hochschulisch qualifizierte Pflegende in der Langzeitversorgung?!

Abstract: Wandel der (pflegerischen) Langzeitversorgung -168 13.2 Situation in Deutschland -169 13.3 Situation im Ausland -171 13.4 Effekte hochschulisch qualifizierter Pflege (in der Langzeitversorgung) -173 13.5 Schlussfolgerungen -174 Literatur -175

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…Previous work shows that higher qualification of nursing professionals is associated with improved patient outcomes [ 38 , 39 ]. Regression analysis did not show a significant correlation between nurses' additional qualification in gerontopsychiatry and a higher risk for the prescription of PIM/antipsychotics to participating patients .…”
Section: Discussionmentioning
confidence: 99%
“…Previous work shows that higher qualification of nursing professionals is associated with improved patient outcomes [ 38 , 39 ]. Regression analysis did not show a significant correlation between nurses' additional qualification in gerontopsychiatry and a higher risk for the prescription of PIM/antipsychotics to participating patients .…”
Section: Discussionmentioning
confidence: 99%
“…4 For these residents, skills of academically qualified nurses could create a meaningful benefit. 5 Academic training enables nurses to combine their clinical expertise with scientific evidence to provide care according to patient's or resident's preferences (evidence-based nursing). 6 Care that is guided by individuals' values and preferences is referred to as person-centred care and can improve patient experiences and outcomes, and enhance the efficiency of healthcare delivery.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Ninety per cent of these hospital transfers are unplanned, and between 4% and 55% are considered avoidable 4. For these residents, skills of academically qualified nurses could create a meaningful benefit 5. Academic training enables nurses to combine their clinical expertise with scientific evidence to provide care according to patient’s or resident’s preferences (evidence-based nursing) 6.…”
Section: Introductionmentioning
confidence: 99%
“…TVPOI represent a very heterogeneous group, especially with regard to their age, ventilator-causing diseases and comorbidities, course of disease and care needs, therapy goals, as well as living and care situations 1–3. In Germany, different care settings for TVPOI exist: inpatient facilities and outpatient care supported by nursing care service providers (eg, in the patient’s own home or in a shared apartment).…”
Section: Introductionmentioning
confidence: 99%
“…Detailed information on intensive care in Germany can be found in box 1 4. However, high costs of medical, rehabilitative-therapeutic and nursing care services,1 5 and an intransparent provider market,3 with increasing evidence of quality deficiencies4 6 7 have been criticised. Studies found indications of medical-therapeutic overuse, underuse and misuse, especially with regard to unused weaning potential,5 8 9 overload of general practitioners,10 lack of therapeutic rehabilitation services11 and qualified specialist nurses,6 7 with regionally varying availability 12.…”
Section: Introductionmentioning
confidence: 99%